Genetic Variation Analysis of EMS-Induced Chili Pepper (Capsicum frutescens L.) Mutants Using SSR Markers - Dwinianti, Edia Fitri; Mastuti, Retno; Arumingtyas, Estri Laras (Journal of Tropical Life Science, 2019)
Mutation induction with chemical mutagen ethyl methane sulfonate (EMS) capable of producing genetic variation in plants. The purpose of this research was to evaluate genetic variation of EMS-induced chili pepper mutants using SSR molecular marker. Various concentration of EMS (0.01%; 0.02%; 0.04%) were applied to chili pepper seeds of Genotypes 2, 7, and 11. The genomic DNA was isolated from mutants and control plants then used for PCR analysis using three SSR primers namely CA26, CA52 and CA96. The three SSR primers were able to detect genetic variation in the three genotypes of EMS-induced chili pepper mutants and control plants. A total of 18 alleles have been identified in all three SSR loci with PIC values ranging from 0.792 to 0.893. The three genotypes of chili pepper plants had different sensitivity to EMS mutation induction. Genotype 11 plants showed higher sensitivity to EMS treatment than genotypes 2 and 7 based on the amount of genomic changes. Dendrogram constructed based on genetic similarity values distributed the mutants and control plants into three main groups with similarity coefficients ranging from 0.34 to 0.90. Similar genotype either control plant or mutants, especially Genotypes 2 and 7 were group into similar group. However, for the Genotype 11 plants, large genome changes cause mutant plants G11K1, G11K2, G11K3 had a low genetic similarity to their control plants, so the mutants were separated in a different group from the control plant. Those indicate that EMS mutation induction capable of increasing genetic variation in chili pepper plants based on SSR molecular marker.